A funcionalidade do letramento em saúde na qualidade de vida e papel do enfermeiro: revisão com análise bibliométrica - MIRANDA, Joana Maria Gomes de (2019)
The term Functional Health Literacy (FHL), or health literacy, aims to promote educational actions in relation to health, that is, the teaching-learning process that encompasses dialogue, more importantly for nurses theoretical-practical skills, cognitive perceptions, specific and essential health care with the client and his / her family, with the purpose of developing an affectionate and trustful bond, without development of each task developed by the nurse. Objective: To identify scientific productions in relation to FHL between the years of 2006 and 2016. Methodology: This research is based on a Review with bibliometric analysis, realized in November 2016. The descriptors "Literacy in Health" and "Health education", covering the period 2006 to 2016 in the portal of Brasil Virtual Health Library (BVS), with the objective of selecting the total number of articles related to the theme. Results: nine (09) articles were obtained from this filter, seven (07) being directly related and two (02) indirectly related. Conclusion: The present study inferred that nurses are an essential part of health promotion, acting as a host, giving care and developing strategies as well as bringing health benefits, functional autonomy and knowledge construction. The results obtained highlighted the importance of the categories, with the result it was possible to conclude that, in the nursing field, collective health presents greater adherence. In short, the precepts of functional literacy in health are based on teaching by doing dialogic workshops, bringing knowledge and information to each audience according to their particularities and needs. We emphasize the nurse as a foster that generates trust, respect, friendship and commitment between patient and caregiver.